AFFIXATION IN THE SCRIPT SONG LYRIC âHALL OF FAMEâ - Meinawati, Euis; Alawiyah, Sufi (Lembaga Penelitian Unswagati Cirebon Indonesia, 2018)
The objective of researchis to analyze affixation in The Script song lyric. The main purpose of this research is to know how affixation process happens in The Script song lyric âHall of Fameâ. The method used in this research isdescriptive qualitative method. The data used the text script oflyric. It will be an object to know how affixation process happens and what the influencescauses by affixation itself. The result of this analysis shows that affixation process dividedintwo types depends on affixes itself.Â Â